(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
Alternations of marine and meteoric diagenetic conditions, most probably caused by relative sea level fluctuations, are recorded in an Upper Triassic (Rhaetian) patch reef in the Calcare di Zu Formation, Lombardian Basin. Three main types of cements have been distinguished: 1)isopachous fibrous calcite cement, partially to completely filling mostly secondary solution cavities; 2) radial-fibrous calcite cement in which strongly turbid relics of precursor fibrous cements suggesting a neomorphic origin can be observed, and 3) equant spar calcite found both as a last cement occluding the remaining void space after the cementation by the fibrous cements and as a neomorphic product in corals. Both marine and non-marine internal sediments are present in the patch reef. The marine internal sediments are composed of fecal pellets, peloids, micrite and bioclasts. They could be precedent, successive or contemporaneous to the isopachous marine cement and could have a geopetal disposition or may completely fill cavities. The observations made indicate that a "peloidal texture" (a nucleus of anhedral HMC crystals from which fibrous crystals radiate) could result from the introduction of peloids/fine-grained micritic intraclasts into fibrous marine cements during their growth. This texture has not been observed in geopetal infill peloids. Non marine internal sediments are composed of crystal silts and their deposition was preceded by the partial dissolution of the isopachous fibrous cements.